Fluid machine system design / Abdul Samad Mohd Ibrahim - Mohd Ibrahim, Abdul Samad (1990)
This report is basically the designing of fluid machine system using a Francis Turbine. We carried out our design starting from the Francis Turbine that has already existed in the laboratory but the efficiency is no or due to non constant head while "operating. We have come to conclusion that the designing of the system is buying a self-contained unit. The objective of this design is to get a constant head while the pump and the turbine are on elating.-Furthermore it is an opportunity for us to study about —turbomachinery. The designing of a fluid system is perhaps the most practical and most active application of the principle of fluid mechanics. Also in this project we have to consider all the losses throughout the system proposed. By considering this factor we have to make a selection of pipe, valve, pump etc. Itis also wisely stated here that 'this design could be the proposal of: fluid system at the Fluid Mechanic Laboratory in TTM, Shah Alam.